2021
DOI: 10.1108/amhid-11-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic prescribing for patients with intellectual disabilities and challenging behaviours

Abstract: Purpose Review of antipsychotic prescribing practices, rationale and follow-up using an internationally standardized audit can be an effective tool to encourage and monitor best practices. The purpose of this study is to audit the current prescribing pattern for people with intellectual disabilities and challenging behaviours in Qatar. Design/methodology/approach This study was based on the challenging behaviour management guidelines recommended by the Royal College of Psychiatrists. All current electronic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, the severity of his challenging behaviors might have led to him being placed on antipsychotic medication as part of the risk management plan and treatment for challenging behavior. 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the severity of his challenging behaviors might have led to him being placed on antipsychotic medication as part of the risk management plan and treatment for challenging behavior. 20 …”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the cerebellar lesion played a significant role in the presence of impulsive behavior in our patient’s case, as previous clinical studies of patients with posterior cerebellar lesions reported difficulties controlling their behavior and emotions, language deficits, and lack of concentration. 20 22 Furthermore, cerebellar cognitive affective syndrome is characterized by executive function deficiencies accompanied by disinhibited and inappropriate behavior, socially aberrant behavior, personality changes, and language impairments. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that caregivers used several coping strategies concurrently and were most likely to use religion, acceptance and active coping styles in relation to their perceived stress. Although a recent study in Qatar looked at prescription patterns among adults with intellectual disabilities and challenging behaviour ( Elhusein et al, 2021 ), however, this is the first study to examine the perceived stress levels and coping strategies of caregivers of adults with intellectual disability and challenging behaviours in the state of Qatar, there were no similar studies for comparison.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Finally, in Oman and the wider Arab region, there is a need for culture-specific psychoeducation to address the contextual and socio-religious factors and stigma to improve access to mental health services. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%